Influence of electronic commerce on the real estate industry in Singapore - Ang, Hwee Jin (2008)
This research will focus on how the real estate industry in Singapore is affected by e-commerce. A survey on the pervasiveness of e-commerce in Singapore has also been conducted. This survey allows readers to gain a valuable insight into the factors influencing the decisions to adopt e-commerce.